Join the QuestionCove community and study together with friends!

Sign Up

OpenStudy (anonymous):

I meant 1/81, sorry

OpenStudy (anonymous):

I don't quite understand how you got the answer, please feel free to explain!

OpenStudy (anonymous):

Eyad explain her,please

OpenStudy (anonymous):

Here is the law of changing :
\[\Large Log_{a}b=c \]
TO change that in to exponential :
\[\Large a^{c}=b\]

OpenStudy (anonymous):

Oh okay! I understand now, thanks!

Still Need Help?

Join the QuestionCove community and study together with friends!

Sign Up

OpenStudy (anonymous):

I have just one more question, if that's okay?

OpenStudy (anonymous):

Sure ,Feel free to ask anything :P

OpenStudy (anonymous):

Step 1:\[4^{x-1}=64^{x+3}\]Step 2:\[4^{x-1}=(4^{3})^{x+3}\]Step 3:\[4^{x-1}=4^{3x+9}\]
What would be the next step?
A. 4 = 3x + 9
B. x - 1 = -(3x + 9)
C. x - 1 = x + 3
D. x - 1 = 3x + 9

OpenStudy (anonymous):

Since Base (4) = Base (4)
therefore power =power
which mean X-1=3x+9

OpenStudy (anonymous):

Okay! Thank you, again!

Still Need Help?

Join the QuestionCove community and study together with friends!